2020
DOI: 10.1186/s42787-019-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Hall and ion slip effects on Unsteady MHD Convective Rotating flow of Nanofluids—Application in Biomedical Engineering

Abstract: There is an intense worldwide activity in the development of instrumentation for medical diagnosis and bioscreening based on biological labeling and detection of nanoparticles. Based on this profound observation, Hall and ion slip effects on magnetohydrodynamic (MHD) free convective rotating flow of nanofluids in a porous medium past a moving vertical semi-infinite flat plate are investigated. The equations for governing flow are solved analytically by perturbation approximation. The effects of various paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 231 publications
(65 citation statements)
references
References 28 publications
1
64
0
Order By: Relevance
“…Ellahi et al [27] studied the impacts of entropy generation and radiation on MHD nanofluid flow of through a wavy channel and revealed that the lower wall of channel energy was reduced due to radiation parameter. The studies related to the characteristics of heat transfer of various MHD nanofluids flow due to different geometry were performed by [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Ellahi et al [27] studied the impacts of entropy generation and radiation on MHD nanofluid flow of through a wavy channel and revealed that the lower wall of channel energy was reduced due to radiation parameter. The studies related to the characteristics of heat transfer of various MHD nanofluids flow due to different geometry were performed by [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The solution of displayed hydrodynamic boundary layer flow is obtained via the Galerkin finite element method (GFEM). Other most recent investigations on Hall and ion‐slip impacts are given in References 32‐40 …”
Section: Introductionmentioning
confidence: 99%
“…Hall and ion-slip effects on unsteady MHD convective rotating flow of nanofluids have been discussed by Veera Krishna and Chamkha. 21 Veera Krishna 22 investigated the heat transport on a steady MHD flow of copper and alumina nanofluids past a stretching porous surface. Veera Krishna et al 23 investigated the Hall and ion-slip effects on the unsteady MHD free convective rotating flow through porous medium past an exponentially accelerated inclined plate.…”
Section: Introductionmentioning
confidence: 99%
“…Veera Krishna and Chamkha 20 discussed the MHD squeezing flow of a water‐based nanofluid through a saturated porous medium between two parallel disks, taking the Hall current into account. Hall and ion‐slip effects on unsteady MHD convective rotating flow of nanofluids have been discussed by Veera Krishna and Chamkha 21 . Veera Krishna 22 investigated the heat transport on a steady MHD flow of copper and alumina nanofluids past a stretching porous surface.…”
Section: Introductionmentioning
confidence: 99%